Positive diagnostic positional tests in BPPV are higher in the morning than in the afternoon: a retrospective study - Lu, Qiuping; Zhan, Ting; Xu, Jiabao; Chen, Huihong; Zhou, Jinzhang; Liu, Huaifeng; Yang, Tinglong; Strupp, Michael; Zhang, Biru (Frontiers in Neurology, 2025)
ObjectivePositional tests are the standard for diagnosing benign paroxysmal positional vertigo (BPPV). We evaluated the relationship between the timing of the testing during the day and the rate of pathological findings.MethodsA retrospective analysis of clinical records from 929 patients with a medical history consistent with the diagnosis of BPPV from Jan 1st, 2023 until Dec 31st, 2024 was performed. The aim was to assess timing of examinations and diagnostic findings. Morning examinations were categorized as those initiated from 8 a.m. to 12 p.m., while afternoon examinations were defined from 2 p.m. to 5 p.m. The rate of pathological positional tests was evaluated based on the observation of positional nystagmus induced by the diagnostic maneuvers.ResultsA total of 929 individuals with the presumed diagnosis of BPPV were examined by diagnostic positional maneuvers. Five hundred and ninety individuals (63.51%) were examined in the morning and 339 (36.49%) in the afternoon. The positive rate of BPPV testing was 72.54% (428/590) in the morning group and 64.01% (217/339) in the afternoon group (P < 0.01). Subgroup-analysis by semicircular canal type showed the number of posterior semicircular canal BPPV (pcBPPV) was 308 of 590 (52.20%) in the morning and 154 of 339 (45.43%) in the afternoon, with a significant difference (p = 0.010). For horizontal semicircular canal BPPV (hcBPPV), the number was 115 of 590 (19.49%) in the morning and 60 of 339 (17.70%) in the afternoon (p = 0.080). Hourly analysis for both canal types revealed the highest positive rate (74.6%) between 8:00 a.m. and 8:59 a.m. and lowest (51.9%) between 2:00 p.m. and 2:59 p.m., with higher positive rates in the morning (p = 0.005). Multi-variate analysis showed a strong association with examination timing (p = 0.005) with no correlation between age/gender and positive testing.ConclusionThe overall positive rate for positional tests for BPPV was significantly higher in the morning than in the afternoon. Subgroup analysis showed a statistically difference for pcBPPV but not for hcBPPV. These findings hold clinical implications for optimizing examination scheduling and improving diagnostic and treatment strategies for patients with vertigo. Prospective studies are warranted to validate the reliability and validity of these observations.